The Relative Frequency of Haemophilia A and B - Jung, Ernst G. (Thrombosis and Haemostasis, 1960)
Two tables show the haemophilia cases observed in Zurich and the relative frequency of haemophilia A and haemophilia B in Switzerland and some other countries.